2011
DOI: 10.1007/s11302-011-9234-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diadenosine tetraphosphate on FGF9-induced chloride flux changes in achondroplastic chondrocytes

Abstract: Achondroplasia, the most common type of dwarfism, is characterized by a mutation in the fibroblast growth factor receptor 3 (FGFR3). Achondroplasia is an orphan pathology with no pharmacological treatment so far. However, the possibility of using the dinucleotide diadenosine tetraphosphate (Ap 4 A) with therapeutic purposes in achondroplasia has been previously suggested. The pathogenesis involves the constitutive activation of FGFR3, resulting in altered biochemical and physiological processes in chondrocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…In this buffer, NaCl was replaced by an equimolar concentration of NaNO 3 (Panreac). Plates were then read on Fluoroskan FL fluorescence plate reader (Thermo Labsystems Inc., Waltham, MA) following the methodology described by Huete et al (2011).…”
Section: Methodsmentioning
confidence: 99%
“…In this buffer, NaCl was replaced by an equimolar concentration of NaNO 3 (Panreac). Plates were then read on Fluoroskan FL fluorescence plate reader (Thermo Labsystems Inc., Waltham, MA) following the methodology described by Huete et al (2011).…”
Section: Methodsmentioning
confidence: 99%
“…In other cellular models, achondroplastic chondrocytes, the effect of Ap 4 A was virtually identical. In this model, diadenosine tetraphosphate was also facilitating the efflux of chloride from these cells (Huete et al, 2011). Therefore, it seems that there is a coordinated action triggered by the P2Y 2 receptor after the stimulation by Ap 4 A that produces a mobilization of AQ1 towards the membrane and an increase in the Cl À efflux, which altogether, would be responsible for the P2Y 2 mediated elevation of IOP (Fig.…”
Section: Presence In the Aqueous Humourmentioning
confidence: 69%
“…In a later paper from this group, it was shown that P2Y 1 , P2Y 2 , P2Y 6 and P2Y 11 receptors were expressed by achondroplasic chondrocytes and that Ap 4 A was acting via these P2Y receptors [468]. In a more recent study, they showed that Ap 4 A reversed the morphological changes triggered by FGF9 and restored the chloride efflux, providing further evidence for the therapeutic potential of this dinucleotide in the treatment of dwarfism [469].…”
Section: Dwarfism (Achondroplasia)mentioning
confidence: 90%